Dissimilar laser welding of an AA6022-AZ31 lap-joint by using Ni-interlayer: novel beam-wobbling technique, processing parameters, and metallurgical characterization - Khodabakhshi, Farzad; L. H., Shah; Gerlich, Adrian (Elsevier Ltd, 2019)
In this article, the weldability of dissimilar lap joints between 2 mm thick sheets of AA6022 aluminum (bottom) and AZ31 magnesium alloys (upper) was studied using a fiber laser with a wobbling scanner. The effects of laser beam wobbling parameters, laser power, traveling speed, and the presence of a pure nickel interlayer (∼0.1 mm thickness) is evaluated based on the microstructures and phases produced. The experimental results revealed dissimilar joint formation is highly dependent on inter-mixing, as well as fusion zone dimensions which control Al- and Mg-rich interaction zones that vary with laser power. Sound dissimilar joints were only produced by penetrating the Mg-rich interaction zone into the aluminum alloy. Joint formation benefited from suppression of Al-Mg chemical reactions using a Ni-interlayer, providing more well-dispersed and more benign phases compared to Al-Mg intermetallics at the interface during welding. The application of laser beam wobbling on a circular path with diameter of ∼0.4 mm and frequency of 1000 Hz served to reduce cracks and enhanced materials intermixing.